The Influence of Work Environment and Workload on Employee Performance with Job Satisfaction as a Mediating Variable at Siloam Bali Group - Santihari, Luh Putu Asti; Ary Meitriana, Made; Indah Rahmawati, Putu (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of work environment and workload on employee performance, with job satisfaction as a mediating variable. Using a quantitative ex-post facto approach, data were collected from 138 permanent employees at Siloam Group Bali Area. The analysis employed PLS-SEM. Results show that work environment positively affects job satisfaction and performance, while workload has a negative effect. Job satisfaction mediates the relationship between work environment and performance, but not between workload and performance. These findings highlight the importance of a supportive work environment and effective workload management in enhancing employee performance through job satisfaction.